The role of international organizations in protection the Antiquities of Mesopotamia - Muhammad Saeed, Imad AbdulQadir (Al-Adab Journal, 2019)
The Antiquities of the memory of the nation and its beating heart, it is both material and moral part is an integral part of history and intellectual and cultural heritage as a platform for the dissemination of culture As well as an active component in the rooting of the cultural identity. It also plays a special role in the detection of human knowledge through the ages of the past, and how to achieve gradualization in the process of urbanization since ancient times and for the present time . It is regrettable that archeology, cultural heritage and natural heritage are threatened with constant destruction and destruction. Whether this destruction is organized or unorganized, the disappearance and the disappearance of monuments and cultural heritage is a blow to the heritage of all the peoples of the world, especially as some countries and nations can not protect their monuments and preserve their cultural heritage. , As a result of the lack of economic, scientific and technical resources of one country or another. One of the ways to address this issue and to achieve cooperation, understanding and cultural interdependence between nations and peoples is to resort to some international organizations that have a role in concluding some agreements and recommendations. And the issuance of new provisions in the form of agreements to establish an effective system aimed at protecting the relics and heritage of peoples, and in accordance with modern scientific methods.